ACETAZOLAMIDE IN PEDIATRIC NEUROLOGY: HISTORY AND PERSPECTIVE OF CILNICAL USE - A.N. Boyko; E.I. Gusev; O.V. Bykova; L.M. Kuzenkova; O.I. Maslova (Вопросы современной педиатрии)
Resume the up tob date pharmacological and clinical findings have revealed new opportunities for the use of known for a long time pharmaceutical agents in various fields of practical medicine. For more than 50 years acetozolamide, systemic carbonic anhydrase inhibitor, has been used in neurology to correct liquorodynamic disorders. High clinical efficacy and good tolerb ability in longbterm use has made acetazolamide an essential agent in pediatric neurology, along with this the true therapeutic application of acetazolamide is much wider than it was traditionally thought. This review analyzes the experience of administration of the drug in different branches of pediatric neurology, including those where acetazolamide has been traditionally used along with novel applications to administration of the drug in children.Key words: acetozolamide, carboanhydrase, children, sleep apnea syndrome, glaucoma, hydrocephaly, episodic ataxia type II, migraine, intracranial idiopathic benign hemiplegic hypertension.